22/#211 Survival impact of adjuvant radiotherapy in uterine carcinosarcoma – a seer based study. (4th December 2022) - Jones, Angela; Ramirez, Paulina; Lababidi, Suzanne; Toy, Eugene
Abstract : Objectives: While the role of adjuvant radiotherapy (aRT) has been well-established in the treatment of high-risk endometrial cancer, randomized trial data regarding aRT use in uterine carcinosarcoma (UCS), a rare subtype, is limited. Our objective is to compare the survival impact of aRT versus chemotherapy alone in the treatment of UCS using the Surveillance, Epidemiology, and End Results (SEER) database. Methods: The SEER database was queried for all patients diagnosed with stage II-IV UCS. Patients were excluded who did not undergo surgery and chemotherapy. Survival was analyzed using the Kaplan-Meier method. Multivariate Cox regression analysis was used to evaluate the survival impact of aRT while controlling for patient age, diagnosis year, race/ethnicity, stage, grade, number of positive regional lymph nodes, and tumor size. Results: A total of 2, 362 patients were identified. A significant improvement in cause specific survival (CSS) was noted in patients who underwent combination therapy (vaginal brachytherapy [VB] plus external beam radiation therapy [EBRT]) versus chemotherapy alone (hazard ratio [HR] 0.805, 95% confidence interval [CI] 0.674–0.961, p<0.05). VB and EBRT each given exclusively versus chemotherapy alone resulted in improved overall survival (OS) ([VB HR 0.852, 95% CI 0.788–0.920, p<0.001], [EBRT HR 0.758, 95% CI 0.646–0.889, p=0.001]), but not cause specific survival (CSS). No difference in survival was found in VB or EBRT alone versus combination therapy, or in EBRT versus VB. Conclusions: Combination aRT with chemotherapy shows superior CSS compared to chemotherapy alone. This SEER database study validates aRT use in this rare subset of high-risk endometrial cancer.